Schizophrenia : a practical primer - Keshavan, Matcheri S., 1953-; Srihari, Vinod H.; Reddy, Ravinder (New York, NY : Routledge, 2024)
"This second edition of Schizophrenia: A Practical Primer, includes decades of clinical and research experience in the field and helps readers understand what schizophrenia is and how it is managed. Schizophrenia is a devastating illness that affects more than fifty million worldwide. Written to help anyone who is faced with managing schizophrenia, whether as a clinician, patient, friend, or family member, this accessible book is an ideal first stop for practical, up-to-date information. It includes an overview of schizophrenia and provides answers to common questions that arise on different aspects of the illness, such as: diagnosis, pharmacological and psychotherapeutic management, treatment challenges, and achieving recovery. Beyond these key issues, the book includes developments in the neurobiology of the illness, foreseeable developments and the history of schizophrenia. It also includes brief, realistic case vignettes adapted from clinical experience, and questions interspersed throughout the book to aid understanding. This book is essential for professional trainee and early career mental health workers, such as psychiatrists, psychologists, social workers, counselors, and nurses, and is written to cover in a concise and accessible way what is of immediate and practical relevance to gain familiarity with schizophrenia"--
Keywords: Schizophrenia -- Popular works; MEDICAL / Psychiatry / General; MEDICAL / Neuroscience; MEDICAL / Nursing / General